“Ash” [æ] sound then and now: An overview of the current state of knowledge - Barbara Grobelna (Estudios de Fonética Experimental)
The objective of this article is to review the existing studies on the British Received Pronunciation “ash” [æ] sound, as well as its varia- tions outside the United Kingdom. It starts with a short analysis of sociolinguistic aspects of the Received Pronunciation accent, then it points out the most conspicuous differences between the Received Pronunciation and General American vowel systems. Then, it pre- sents the early beginnings and the further developments of [æ], and finally, it discusses the alternations in the pronunciation of this sound and the most important examples of phonological variations for [æ] outside the UK.